Pengaruh Teknologi Informasi Terhadap akhlak siswa kelas V SDN 147 Pekanbaru - ar mia mia (el-Ibtidaiy:Journal of Primary Education, 2019)
Education of behavior represent especial problems which always become human being challenge in as long as history civilization of nations [in] world. history indicating that a[n nation will be sturdy if its sturdy behavior conversely a[n nation will collapse if its behavior destroy            This research aim to to know what is there [is] influence which are positive [among/between] Penggunaaan Information Technology with student behavior of SD Country 147 Pekanbaru. To obtain;get required [by] data [is] writer use three data collecting technique that is: (1) Enquette, ( 2) Documentation            Population in this research [is] Class student of V [in] SD Country 147 Town of Pekanbaru amounting to 139 student people. Because to the number of population, hence writer take sampel that is 25% from existing population with technique of Proposional Random Sampling. Become sampel of this research that is counted 35 student people. In quantitative data processing, writer of technique cave analyse quantitative approach with technique cave analyse linear regresi with Smallest Square method by using computer program of SPSS Windows version for 18.0  Conclusion that pursuant to reached persetase in this research can know that there is influence which [is] signifikan [among/between] Usage of Information Technology to student behavior. Influence storey;level [among/between] both variable reside in [at] high or strong category with reng ( 0,700 - 0,900), that is equal to 0,794. While coefficient of determinasi( Square R) [is] 0,631, Contribution information technology to student behavior equal to 0,631 X 100 = 63,1 % and rest influenced by other factor. this situation indicate that active progressively student in using Information Technology, hence student behavior progressively shift from behavior of Islami.